The Volta: A Galant Gesture of Culmination. (18th September 2020) - Mitchell, Nathaniel
Abstract: This article presents an overview of a new pre-cadential schema in the galant style: the Volta. The Volta is a two-part schema featuring a prominent chromatic reversal: stage one charges up the dominant with a ♯ 4 ^ – 5 ^ melodic string, while stage two releases to the tonic using a ♮ 4 ^ – 3 ^ string. The schema sheds light on many aspects of galant music-making: its variants illustrate how central features of a schematic prototype motivate or constrain plausible manipulations, its pre-cadential function reveals the intimate communion between surface schemas and the harmonic patterns inscribed within the style's formal scripts, and, finally, its use as a climactic gesture in opera seria calls attention to the semantic possibilities of schemas beyond their role in defining musical topics. These and other aspects of the Volta are illustrated using representative excerpts from eighteenth-century masters like Leonardo Vinci, Giovanni Battista Pergolesi, Johann Adolf Hasse, Baldassare Galuppi, Joseph Haydn, and Wolfgang Amadeus Mozart.